2021
DOI: 10.3390/pathogens10040450
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Pathogenicity in Space

Abstract: After a less dynamic period, space exploration is now booming. There has been a sharp increase in the number of current missions and also of those being planned for the near future. Microorganisms will be an inevitable component of these missions, mostly because they hitchhike, either attached to space technology, like spaceships or spacesuits, to organic matter and even to us (human microbiome), or to other life forms we carry on our missions. Basically, we never travel alone. Therefore, we need to have a cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 131 publications
0
15
0
Order By: Relevance
“…However, more research is required to continue the battle against SARS-CoV-2, and cooperation between governments, academia, and industries is crucial to make this happen [2] . Additional risks of the pandemic can be generated by booming space programs, with hitchhiking Earth’s viruses becoming pathogenic in space [3] or even extraterrestrial viruses infecting humans [4] .…”
Section: Introductionmentioning
confidence: 99%
“…However, more research is required to continue the battle against SARS-CoV-2, and cooperation between governments, academia, and industries is crucial to make this happen [2] . Additional risks of the pandemic can be generated by booming space programs, with hitchhiking Earth’s viruses becoming pathogenic in space [3] or even extraterrestrial viruses infecting humans [4] .…”
Section: Introductionmentioning
confidence: 99%
“…A LEO-based platform could be used to accelerate the timeline for biofouling characterization of biomaterials and elucidate mechanisms that may be altered in microgravity in ways that increase or decrease virulence. In fact, studies have shown that during spaceflight, some bacterial strains appear to exhibit increased virulence ( Simoes and Antunes, 2021 ).…”
Section: Key Opportunities Identifiedmentioning
confidence: 99%
“…Space itself can be seen as an extreme environment, with a combination of multiple conditions and with a range of effects on microbes that are not yet fully explored. Observed changes in the characteristics of pathogens and conditional pathogens in space, namely increased pathogenicity and virulence, are a significant concern when discussing long-term crewed mission or human presence in space (Simões and Antunes, 2021 ). The impact of the space environment seems to vary between species, so the need for further studies has been stressed by several authors.…”
Section: New Frontiersmentioning
confidence: 99%